Phytochemical Screening of Metabolites in the Testa of Peanut (Arachis hypogaea) Extract, Mung Beans (Vigna radiata) Extract, Red Beans (Phaseolus vulgaris) Extract and Congo Beans (Cajanus cajan): Screening of Metabolites of Different Beans (Biological Sciences - PJSIR, 2025)
Phytochemical screening of metabolites was conducted to find out the presence of alkaloids, flavonoids, polyphenols and tannins in the testa of peanut extract of (Arachis hypogaea), mung beans and also (Vigna radiata), red beans (Phaseolus vulgaris) and congo beans (Cajanus cajan) through phytochemical screening. The samples were subjected to various tests Bate-smith and Metcalf method for flavonoids, ferric chloride test for polyphenols, Mayer's test for alkaloids and gelatin test for tannins. The results show that all four samples yielded a positive (+) result for the presence of flavonoids, polyphenols and alkaloids. However, test results for tannins yield a negative results and needs further confirmatory evaluation. Therefore, it can be concluded that the use of these samples as ingredients for various food products may be highly useful to the food processing industry. It is hereby recommended that more parallel studies focusing on the nutritional value of these samples be done complementing the results of this particular research which may be utilized as a baseline data.